Total Ionizing Dose Effects of Si Vertical Diffused MOSFET with SiO2 and Si3N4/SiO2 Gate Dielectrics - Jiongjiong Mo; Xuran Zhao; Min Zhou (Active and Passive Electronic Components)
The total ionizing dose irradiation effects are investigated in Si vertical diffused MOSFETs (VDMOSs) with different gate dielectrics including single SiO2 layer and double Si3N4/SiO2 layer. Radiation-induced holes trapping is greater for single SiO2 layer than for double Si3N4/SiO2 layer. Dielectric oxidation temperature dependent TID effects are also studied. Holes trapping induced negative threshold voltage shift is smaller for SiO2 at lower oxidation temperature. Gate bias during irradiation leads to different VTH shift for different gate dielectrics. Single SiO2 layer shows the worst negative VTH at VG=0 V, while double Si3N4/SiO2 shows negative VTH shift at VG=-5 V, positive VTH shift at VG=10 V, and negligible VTH shift at VG=0 V.